2018
DOI: 10.1200/cci.18.00059
|View full text |Cite
|
Sign up to set email alerts
|

Low Concordance of Patient-Reported Outcomes With Clinical and Clinical Trial Documentation

Abstract: Purpose Health care research increasingly relies on assessment of data extracted from electronic medical records (EMRs). Clinical trial adverse event (AE) logs and patient-reported outcomes (PROs) are sources of data often available in the context of specific research projects. The aim of this study was to evaluate the extent of data concordance from these sources. Patients and Methods Patients enrolled in clinical trials or receiving standard treatment for lung cancer (n = 62) completed validated questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…Taking up the challenge posed by Lazarus et al [4] in ensuring that 90% of virally suppressed patients have good health-related quality of life can be disruptive with respect to how healthcare practitioners interact with patients with HIV. Patient-reported outcomes have been shown to have a higher correlation with patient health status when compared to what clinicians reported [40,41]. This was highlighted in the present study, which showed that PROs helped identify we could hypothesize that patients underwent a "drucebo" effect and were influenced to report symptoms as a result of being asked about a particular symptom [42].…”
Section: Discussionmentioning
confidence: 48%
“…Taking up the challenge posed by Lazarus et al [4] in ensuring that 90% of virally suppressed patients have good health-related quality of life can be disruptive with respect to how healthcare practitioners interact with patients with HIV. Patient-reported outcomes have been shown to have a higher correlation with patient health status when compared to what clinicians reported [40,41]. This was highlighted in the present study, which showed that PROs helped identify we could hypothesize that patients underwent a "drucebo" effect and were influenced to report symptoms as a result of being asked about a particular symptom [42].…”
Section: Discussionmentioning
confidence: 48%
“…Cela permet notamment de réaliser un suivi plus fidèle, moins biaisé par la consultation et surtout plus fréquent, car ne dépendant pas d’un rendez-vous médical. Une étude a notamment mis en évidence la mauvaise concordance entre les informations enregistrées par les professionnels de santé et les PRO [5] . Le National Cancer Institute a ainsi créé un système ePRO gratuit et en ligne afin de générer ses propres questionnaires, basé sur l’échelle Common Terminology Criteria for Adverse Events (CTCAE) [6] .…”
Section: Questionnaires Patients Pro Et Eprounclassified
“…In the case of our study, smoking data were not reliably available, even retrospectively from the electronic health record (EHR). Abstracting data regarding smoking from the EHR is likely not concordant with self‐reported patient reported outcome measures 4 …”
Section: Conflict Of Interestsmentioning
confidence: 99%